Signifikan Etika Akuntan dalam Implementasi Audit Fraud - Lea Berliana Jeni Salih; Dania Salsabela; Tries Ellia Sandari (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Like a professional accountant, in carrying out the audit function, he is obliged to comply with the work code of ethics and audit financial statements through ethical norms or applicable auditing standards. In carrying out work, an accountant must ensure that every action taken is in line with established moral standards. This code of ethics is based on the goal of maintaining public confidence in high quality services, regardless of who is performing those services. including their expert practice, fraud auditors are also obliged to implement the rules and ethics that are of interest to them, as a manifestation of the public's confidence in the integrity of the accounting profession. While performing all phases of a fraud audit, fraud auditors must still adhere to the applicable ethical rules. Basically, they must demonstrate an attitude of diligence and honesty in carrying out audit tasks to ensure objective and accountable results.